Sexual Dimorphic Metabolic Alterations in Hepatitis C Virus-infected Patients: A Community-Based Study in a Hepatitis B/Hepatitis C Virus Hyperendemic Area. Issue 18 (May 2016) - Hu, Jing-Hong; Chen, Mei-Yen; Yeh, Chau-Ting; Lin, Huang-Shen; Lin, Ming-Shyan; Huang, Tung-Jung; Chang, Ming-Ling
Abstract : Abstract: The impact of sex on metabolic alterations in individuals with hepatitis B virus (HBV) or hepatitis C virus (HCV) infection remains elusive. A community-based study was performed to assess sex, age, body mass index, the lipid profile, blood pressure, glucose, alanine aminotransferase, HBV surface antigen (HBsAg), and HCV antibody levels, smoking and alcohol drinking habits, and cardiometabolic diseases, including diabetes, hypertension, cardiovascular events, and renal diseases. The HCV-RNA level and genotype were further assessed in HCV antibody-positive subjects, and the hepatitis B e antigen and HBV-DNA levels were further examined in HBsAg-positive subjects. Among the 10, 959 adults enrolled, 1949 (17.8%) and 1536 (14.0%) were HBV and HCV-infected, respectively. Univariate and multivariate analyses showed that the lipid profile and hypertension were independently associated with HCV infection (95% confidence intervals of odds ratios [OR 95% CI]: total cholesterol [TC] = 0.508–0.677; triglycerides = 0.496–0.728; hypertension = 0.669–0.937), but not with HBV infection. Consistently, HCV, but not HBV infection, was negatively associated with the TC and triglyceride levels (OR 95% CI for TC: 0.450–0.601; triglycerides: 0.443–0.671). Generalized linear models revealed that HCV infection, sex, and age interactively affected the lipid profile (OR 95% CI TC = 1.189–1.385; triglycerides = 1.172–5.289). Age-stratification analysis showed that the lipid levels were lower in both the HCV-positive females aged ≥49 years (TC, P < 0.001; triglycerides, P = 0.001) and males of all ages (TC, P < 0.001; triglycerides, P < 0.001) compared with their sex and age-matched HCV-negative counterparts. HCV infection was associated with a higher body mass index (≥49 years, β = 0.405, P = 0.002) and increased rates of cardiovascular events (<49 years, OR 95% CI 1.23–9.566), diabetes (≥49 years, OR 95% CI 1.114–1.932), and renal diseases (≥49 years, OR 95% CI 1.23–9.55), and with a lower rate of hypertension (≥49 years, OR 95% CI 0.616–0.964) in the females, but not in the males, as determined by multivariate analyses. Only HCV infection was associated with metabolic alterations in this HBV/HCV-hyperendemic area. Females aged ≥49 years and males of all ages exhibited HCV-associated hypolipidemia. HCV-associated cardiometabolic diseases were evident only in the females. Sex dimorphism in HCV-associated metabolic complications warrants personalized follow-up of HCV-positive patients. Abstract : Supplemental Digital Content is available in the text